New trends in tailoring active sites in zeolite-based catalysts - Shamzhy, Mariya; Opanasenko, Maksym; Concepción, Patricia; Martínez, Agustín (Chemical Society reviews, 2019)
This review addresses the recent developments and trends in tailoring the nature and local properties of active sites in zeolite-based catalysts, with a special focus on novel extra-large pore, layered (2D), nanocrystalline, and hierarchical (mesoporous) zeolites with enhanced pore accessibility. In the first part of the review, we discuss the latest achievements in the bottom-up (direct synthesis) and top-down (post-synthesis) approaches for isomorphous substitution in zeolites enabling control over the type (Brønsted, Lewis, or both), amount, strength, and location of acid sites. The benefits in catalysis provided by such zeolites with tuned acidity and improved accessibility are shown for different acid-catalyzed reactions involving bulky molecules, as in the synthesis of fine chemicals and biomass transformations. The incorporation of metal species of different sizes (increasing from single atoms to clusters and to nanoparticles) in zeolites allows expanding the set of reactions catalyzed by these materials. The main preparation strategies for designing metal-zeolite catalysts, especially those offering control over the size of the metal species, and their catalytic behaviour in industrially relevant and emerging sustainable catalytic processes are dealt with in the second part of the review. Particular attention is paid to the stabilization of size-controlled small metal clusters and nanoparticles through their encapsulation in the voids of zeolite frameworks as well as to the dynamic behaviour of the metal species under reactive environments with important implications in catalysis. The need for using advanced operando spectroscopic and imaging tools to unveil the precise nature and functioning of the active sites in working zeolites is emphasized. The information gathered in this review is expected to provide guidance for developing more efficient zeolite-based catalysts for existing and new applications.